Convergent and Biomimetic Enantioselective Total Synthesis of (−)-Communesin F - Lathrop, Stephen P. (J Am Chem Soc, 2016)
The first biomimetic enantioselective total synthesis of (−)-communesin F based on a late-stage heterodimerization and aminal exchange is described. Our synthesis features the expedient diazene–directed assembly of two advanced fragments to secure the congested C3a–C3a′ linkage in three steps, followed by a highly efficient biogenetically inspired aminal reorganization to access the heptacyclic communesin core in only two additional steps. Enantioselective syntheses of the two fragments were developed, with highlights including the catalytic asymmetric halocyclization and diastereoselective oxyamination reactions of tryptamine derivatives, a stereoselective sulfinimine allylation, and an efficient cyclotryptamine–C3a-sulfamate synthesis by either a new silver–promoted nucleophilic amination or a rhodium–catalyzed C–H amination protocol. The versatile synthesis of the fragments, their stereocontrolled assembly, and the efficient aminal–exchange as supported by in situ monitoring experiments, in addition to the final stage N1′-acylation of the communesin core provide a highly convergent synthesis of (−)-communesin F.